Maleficient’s horn like appearance myxomatous fusiform aneurysm of the right middle cerebral artery: An evil caused by the atrial myxoma. - Khoirul Hadi (The Interventionalist Journal, 2023)
Atrial myxoma is the most common neoplasm of the heart which consist of 50% of the total cases reported and tend to seed peripherally after operation(1). When the dissemination occurred in the brain, patient normally presented with stroke symptoms due to tumour embolism. However, cerebral aneurysm due to metastatic deposit after atrial myxoma incision is rare. In a study by M. Anvari et al showed that the most common presentation of atrial myxoma is shortness of breath (63%), followed by chest pain (37%) and neurological symptoms, which is mostly related to stroke (26%)(2). In some cases, patient presented with constitutional symptoms like loss of weigh and appetite and some with anaemic symptoms(2). Size of the lesion mainly related to the local symptoms due obstruction of the blood flow in the heart, but the rate of dissemination is depending on the mobility of the lesion(3). Histologically, mayo clinic has divided the tumour based on its gross anatomy into solid and papillary type. The solid type is normally larger and causing obstructive symptoms, however papillary type is the one that tends to embolise peripherally(4). Atrial myxoma can be diagnosed by echocardiogram and mostly located within the left atrium, specifically within the fossa ovalis in 75% of the cases (3). In some cases, MRI is needed to confirm the diagnosis because sometimes thrombus, vegetation or primary lymphoma of the heart might mimic the tumour. In a case of brain dissemination, the stroke due to embolization can be detected via plain CT brain as it will show multifocal infarction predominantly at the cortimedullary junction which is not specific to the arterial territory. As the dissemination occurred at the vessel wall, it can lead to aneurysm formation which can be detected by plain CT brain and confirmed by MRI or cerebral angiogram. We are reporting a case of multiple fusiform cerebral aneurysm 9 years after left atrial myxoma operation.